Co-operative : 'from controls to a regulatory framework' policies for the SAARC region - Chopra, Sanjeev (ed.) (Dehradun, 1999)
The issues examined in this book and the recommendations made shall form the backdrop for future action plans to be charted in the co-op sector, which is a major player in the agriculture & allied sectors in the SAARC countries, and has played a vital role in empowering the rural poor and helping transform the face of the rural areas.
Keywords: SAARC